1990
DOI: 10.1111/j.2044-835x.1990.tb00856.x
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of ethnic sensitivity among Northern Ireland schoolchildren

Abstract: The utility of the release from proactive interference paradigm as a technique for the indirect assessment of ethnic sensitivity was explored. Children in Northern Ireland, aged 7 and 11, recalled sets of names that changed in religious affiliation between the third and fourth sets. Only the older age group demonstrated the predicted improvement in recall following change in name type, findings consistent with studies that have taken approaches to the assessment of ethnic sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Qualitative interviews in the post-accord setting found that some children can identify a limited number of conflict-related social category symbols as young as three years old (Connolly et al, 2002). This finding supports research during the Troubles which found children were sensitised to group symbols and markers, such as colours, occupations, and names (Cairns, 1980(Cairns, , 1987Houston et al, 1990;Jahoda & Harrison, 1975). Collating the markers across this previous work, as well as publications since the Troubles (McKeown & Taylor, 2017), a wide-range of symbols that primary school-aged children might encounter are tested (Reidy et al, 2015).…”
Section: Current Studysupporting
confidence: 77%
See 1 more Smart Citation
“…Qualitative interviews in the post-accord setting found that some children can identify a limited number of conflict-related social category symbols as young as three years old (Connolly et al, 2002). This finding supports research during the Troubles which found children were sensitised to group symbols and markers, such as colours, occupations, and names (Cairns, 1980(Cairns, , 1987Houston et al, 1990;Jahoda & Harrison, 1975). Collating the markers across this previous work, as well as publications since the Troubles (McKeown & Taylor, 2017), a wide-range of symbols that primary school-aged children might encounter are tested (Reidy et al, 2015).…”
Section: Current Studysupporting
confidence: 77%
“…For the open sorting task, 38 images (19 pairs of symbols: one hypothesized to be from each community background) were utilized. These images were drawn from previous research on symbols in NI, both during and after the Troubles (Cairns, 1980(Cairns, , 1987Connolly et al, 2002;Houston et al, 1990;Jahoda & Harrison, 1975;Leonard & McKnight, 2011;Moeschberger & Phillips DeZalia, 2014;Sugden & Bairner, 1986), and were also selected to represent a wider range of the social ecology . Image pairs were organized into three subsections: neighbourhoods and flags (7 pairs; e.g., British flag/Irish flag), sports and activities (6 pairs; e.g., Gaelic football/Rugby ball), and community and religion (6 pairs; e.g., Minister/Priest) (see On-line Appendix at Author Identifying Website).…”
Section: Methodsmentioning
confidence: 99%
“…The authors also found that these attitudes became more polarised with age. Age‐related differences in children's awareness of society's divisions were also found in studies by Cairns (1980), McWhirter and Gamble (1982) and Houston and others (1990), the findings of which reached a broad consensus that children do not develop consistent attitudes towards religion/ethnic discriminations until the ages of 10 and 11 years.…”
Section: Introductionmentioning
confidence: 54%
“…The development of social categorization was not influenced by whether children were from the majority or minority group in their neighborhoods. Using a similar name‐recall task, Houston, Crozier, and Walker (1990) confirmed that most children do not acquire the skill of making ethnic discriminations based on names until they were at least 11 years old.…”
Section: The Researchmentioning
confidence: 75%